Antiseptic properties of aminoadamantane derivative - N. O. Vrynchanu; V. L. Makitruk; A. S. Shalamay; M. L. Dronova; D. M. Dudikova; Z. S. Suvorova; A. O. Sharova (The State Expert Center of the Ministry of Health of Ukraine, 2018)
Development of microbial resistance to current antimicrobial drugs created a critical need of the new antiseptics. The object of our study was phenyladamantane derivative (4-(adamantyl-1)-1-(1-aminobutyl)benzol, AM-166). The aim of the presented study was to investigate the specific activity of 4% AM-166 solution in isopropanol and 5% AM-166 solution in 76% ethanol (manufactured by PJSC SIC «Borshchahivskiy CPP») against the wide spectrum of bacteria and fungi, and effective concentrations and exposition time determination. Desinfectant/antiseptic activity was evaluated by quantitative suspension method with subsequent neutralization. Our results showed that both solutions exhibited similar activity against gram-positive and gram-negative bacteria as well as against yeasts. Antibacterial and antifungal action was demonstrated for all investigated concentrations (initial solution, 5-fold and 10-fold dilutions), observed effect was maintained throughout the whole observation period (from 5 to 30 min). Tested solutions in initial concentrations demonstrated fungicidal activity against A. niger. 5-fold dilution of 5% AM-166 solution in 76% ethanol was more effective than 5-fold dilution of 4% AM-166 solution in isopropanol. 10-fold dilutions of both solutions were ineffective against A. niger. The data obtained suggest the prospects of adamantane derivatives for the development of novel antiseptics.